Revisiting the pH-gated conformational switch on the activities of HisKA-family histidine kinases - Cristina Mideros-Mora (Nature Portfolio, 2020)
Bacterial two-component systems are composed of a sensor histidine kinase (HK) and an effector response regulator and upon signal detection, the HK autophosphorylates a conserved His residue. Here the authors structurally and functionally characterise two HKs, HK853–RR468 and EnvZ–OmpR, and find that the rotamer of the phosphorylatable catalytic His is not influenced by the environmental pH, ruling out an earlier proposed pH-gated model.